Horizontos (kuklos). - van Bladel, Remco; Eekhout, Elise; Meeus, Janna; Academie St-Joost, Breda (Breda : Academie St-Joost, 2001)
Haynes, Elisabeth ; Kuipers, Martien ; Maas, Linda ; Martina, Shahaira ; Minten, Twan ; Tops, Niek-Jan ; Mulder, Christian ; van Tuijn, Erik ; Verbeek, Harrie ; et al.
Eindexamencatalogus, Breda, Academie St. Joost, juni 2001
kunstcatalogus